En ungdomspark planeras - Jaanivald, Maela (2007)
Often places for children and youth are planned how adults think children and adolescents want them, but we are often wrong. As a result, we find empty playgrounds while our target groups are building dens in the bushes, hanging around shopping areas, and so on. This report is an attempt to create a place for young people based on the opinions of their needs and their environment to better understand how to design a place that suits them well. To gain knowledge about how it is to be young in Simrishamn, a small township in the southwest of Sweden, I interviewed children and young adolescents. The interviews were all carried out in groups, mostly in larger groups inside where the result differed a lot depending on the settings for the interview. Two walkabouts with groups of three children were also made. Most of the children were eager to participate and tell about their reality, but some preferred not to. There were also times when the purpose of the interviews was questioned by the youth. The interviews have been processed to a picture of the reality for the children and adolescents involved, focusing on their spare time and outdoor activities. Their description has also been supported by literature on the subject. Both adolescents and children are asking for more arranged activities and places where they can meet, preferably in the presence of some adults. But they are also inquired about outdoor places where the adolescents can be without disturbing neighbors that chase them away. Based on the material, I redesigned Jonebergsparken to a park with youth as the main target group. While the park already had a new playground accessible for disabled children, which shouldn't be moved, I designed this part of the park targeting children. This resulted in a park to grow in, where it's possible for different groups to meet. 5